Analisa Kinerja Algoritma C4.5 Dalam Menentukan Pola Dominasi Mainstream Mahasiswa - Anggraeni, Dewi; Christy, Tika (STMIK Budi Darma, 2019)
The study program is a unit of education and learning activities that has a curriculum and learning method. Each studi program ga a curriculum, in which the curriculum is a set regulatory plans to achieve graduate learning outcomes, study material, processes and assesments that are used as guidelines for the implementation of study program. The main stream of elective and talents. C4.5 algorithm is one method of algorithm that has a decision tree or decision tree, by utilizing data from academics about the selection of the mainstream courses. Bases on the result of the study, the analysis of C4.5 algorithm in determining the pattern of student dominance shows the 73% can be used as a reference marerial in determining student interests and talents